Chandler wobble excitation by catastrophic flooding of the Black Sea - E. Boschi; L. Alfonsi; G. Spada (Annals of Geophysics, 1999)
It is now widely accepted that during the late Quaternary glaciation the Black Sea formed an isolated inland lake (Ross et al., 1970). New geological data and the recognition of sudden population movements away from the Black Sea coasts suggest that the basin was rapidly flooded through the Bosphorus sill 7150 years bp, causing a sea level rise of ~ 135 m in a few years (Ryan et al., 1997). As shown here, such a catastrophic redistribution of mass has significantly altered the amplitude of the Chandler wobble, the free motion of the pole of rotation around the main inertia axis of the Earth (Lambeck, 1980). We also estimate that during the flooding the pole of rotation was diverted from its secular path and shifted by ~ 30 m, at a rate of several meters per year. These rotational variations are found to be orders of magnitude larger than those produced by other short-term geophysical processes, such as earthquakes seismic moment release (O'Connell and Dziewonski, 1979; Chao et al.,1996), anthropogenic water impoundment (Chao, 1995), and tectonic mass movements (Alfonsi and Spada, 1998). The Black Sea flooding may thus be responsible for the most drastic change in the rotational parameters of the Earth in the recent history of our planet.